Species composition and structure of complex of phytonematodes of ornamental plants under conditions of Kiev Goloseevskiy park - Babich, A.A.; Babich, A.G. (Rossijskij parazitologičeskij žurnal, 2019)
The purpose of the research: study of fauna phytonematodes of ornamental crops. Materials and methods. Studies were conducted in 2016-2017 years in Kiev Goloseevskiy park, Ukraine. Materials for studies were samples of soil, plants, larvae and adult nematodes. Production of temporal and permanent preparations, determination of nematode species composition were conducted according to common methods. Results and discussion. 41 phytonematode species belonging to 29 species, 16 families and 5 series were found in rhizosphere of ornamental plants of Goloseevskiy park. According to taxonomic structure 49% species of ornamental plant phytonematode complex belong to Tylenchidae, 36% - to Rhabditida, 7% - to Dorylaimida, 4% - to Enoplida and 4% - to Araeolaimida. It is reasonable to divide species of nematodes found in rhizosphere of plants into 4 groups: phytohelminths, micohelminths, saprobionts and predaceous species. Phytohelminths are 11 species, micohelminths are 7 species, saprobionts are 20 species and 2 species are predaceous speciesof nematodes. Cassagnau index was used in order to determine the state of dominance of dispersed species of nematodes (Cassagnau, 1947). According to this parameter Helycotylenchus dihystera, Aphelenchoides fragarie and Ditylenchus dipsaci were the predominate phytoparasitic species. The following species which we often found were: Tylenchorhynchus dubius, Pratylenchus penetrans, P. pratensis, D. destructor, Paratylenchus nanus, Rotylenchus robustus, A. ritzemabosi, species which we found rarely was Longidorus elongatus.